Different kettles of fish: Varying patterns of antibiotic use on pig, chicken and fish farms in Lao PDR and implications for antimicrobial resistance strategies. Issue 6 (2nd December 2022) - Poupaud, Mariline; Goutard, Flavie Luce; Phouthana, Vannaphone; Muñoz Viera, Facundo; Caro, Domingo; Patriarchi, Alessandro; Paul, Mathilde C.
Summary: The rapid intensification of the livestock sector in Southeast Asia has been found to be associated with an expanding use of antibiotics (ABU) and the rise of antimicrobial resistance (AMR) in both humans and livestock. This study aimed to explore the views and practices of commercial pig, poultry and fish farmers regarding antibiotics in Lao People's Democratic Republic, where data on antibiotic use and AMR remain scarce. A multistage cluster sampling method, based on the random selection of villages in two provinces of Vientiane, was used. A total of 364 farmers, corresponding to 454 farm units, were surveyed using a questionnaire and farm visits. This study found a widespread use of antibiotics (261 out of the 454 farm units used antibiotics). The predominance of antibiotics considered critically important antibiotics for human medicine was of great concern. Results from a logistic regression model showed that antibiotics were found less frequently in fish farm units compared to pig and poultry farm units, and more frequently in specialized farms than in livestock‐fish farms. Multiple factor analysis and hierarchical cluster analysis revealed three profiles of farmers, each with distinct patterns on knowledge, attitudes and practices regarding ABU and AMR. Cluster 1 held a positive attitude regarding preventive measures and information about antibiotics. In cluster 2, there was a view that antibiotics should be used for prophylactic treatment such as disease prevention. Cluster 3 was characterized by farmers with weak knowledge who were unfamiliar with antibiotics and uncertain about details concerning antibiotic use. This cluster was associated with a significantly lower use of antibiotics than the two other clusters in the regression model. The results of this study may help the Laotian government to adapt strategies to control AMR by focusing on the use of critical antibiotics and prophylactic treatments and by tailoring measures to farmers' profiles.